A Differences in the Effectiveness of Relaxation Therapy, Warm Foot Soat With a Mixture of Salt and Legram and Finger Relaxation Therapy for Hypertension Sufferers: Case Study - Dewi Hajar Khansa Amirah; Asep Iskandar; Koernia Nanda Pratama (International Journal of Biomedical Nursing Review, 2023)
Introduction: Hypertension is a disease characterized by an increase in systolic where the results of blood pressure measurements reach more than 140 mmHg and in diastolic reach more than 90 mmHg. The incidence of hypertension in the elderly has increased in line with the increase in age group. Overall, the incidence of hypertension among the elderly in Indonesia is 26.5%. Hypertension can cause various complications if not controlled. Not wanting to take drugs and stress are the causes of uncontrolled hypertension in the elderly. Therefore, an alternative therapy is needed to control blood pressure in the elderly, namely by soaking feet in warm water with a mixture of salt and lemongrass and finger-holding therapy. Purpose: To determine the difference in the effect of warm water foot soak therapy with a mixture of salt and lemongrass and finger grip therapy in controlling blood pressure in the elderly. Methods: The method used in this research is a case study based on evidence based practice. Discussion: Based on the results of the study showed that there was a decrease in blood pressure at systole by 37 mmHg and by 12 mmHg at diastole on Mrs. W who has been given therapeutic intervention by soaking feet in warm water with a mixture of salt and lemon grass. Meanwhile, there was a decrease in blood pressure at systole by 45 mmHg and by 13 mmHg at diastole on Mrs. P who has been given finger-held relaxation therapy. In addition, there was a decrease in Mrs.'s stress level. W, which was originally 16, became 14 (down 2 levels) and at Mrs. P which was originally 19 to 15 (down 4 levels). These results indicate that finger-hold relaxation therapy is more effective in controlling blood pressure and stress levels compared to warm water foot soak therapy with a mixture of salt and lemongrass. No negative side effects were felt by both clients during the intervention. Conclusion: Intervention finger hold relaxation therapy was more effective in controlling blood pressure and stress than warm water foot soak therapy with a mixture of salt and lemongrass.